Integration between healthy and microbiome in holstein cows immediately after calving - Tardón, Daniela Irlanda Castro (2020)
Integration between healthy and microbiome in holstein cows immediately after calving The transition period includes physiological events such as parturitium, colostrogenesis and lactogenesis, which requires the activation of homeorrectic mechanisms to meet the energy demands imposed at this stage of the production cycle. The inadequate adaptation of the cow in the period can evolve to negative energetic balance, metabolic diseases, immunosuppression and high risk for infectious diseases. In this scenario, it is feasible to believe that the cow\'s microbiota undergoes important changes in different colonization sites, and as a cause or effect it interferes with the health of the host. The general objective of this research was to evaluate the correlations between metabolic parameters and the health status of the mammary gland with the microbiota of dairy cows immediately after calving. Blood samples were obtained from 20 multiparous Holstein cows for the determination of metabolic biomarkers, in addition to colostrum, feces and vaginal swabs to perform the metagenome. Archaea kingdom were only found in fecal and vaginal samples. Fecal samples showed a greater abundance of Firmicutes, followed by Bacteroidetes and Actinobacteria. Vaginal samples showed dominance of Firmicutes followed by Bacteroidetes and Proteobacteria. The colostrum microbiota, on the other hand, showed a predominance of Proteobacteria, followed by Firmicutes and Bacteroidetes. At the family taxonomic level, Ruminococcaceae was detected as the most abundant, followed by Bacteroidaceae, Lachnospiraceae and Clostridiceae in fecal and vaginal samples. On the other hand, the predominant families detected in the colostrum samples were Pseudomonadaceae, Staphylococcaceae and, to a lesser extent, Enterobacteriaceae. A positive Spearman correlation was observed between BHB and NEFA with Oscillospira, Treponema, Bacteroides and Methanocorpusculum (Archaea) bacteria. On the contrary, the genus Lactobacillus and Lachnospiraceae showed a negative association with the score of body condition, BHB and NEFA. In colostrum samples, the bacterium of the genus L7A-E11 showed a positive Spearman correlation with somatic cell count (SCC) and a negative correlation with biomarkers of energy metabolism. The Coprococcus and Treponema showed negative correlations with albumin, total protein, triglycerides and cholesterol. Finally, the Clostridiaceae had a positive correlation with the milk production of the cows. The analysis of vaginal samples showed that Methanocorpusculum had a positive correlation with biomarkers of energy metabolism, while Prevotella and L7A.E11 were negatively associated with these markers. The analysis of the entire ecosystem showed that the parameters associated with metabolism, mainly NEFA and BHB, are associated with some bacterial genera, mainly in fecal and vaginal samples from Holstein cows immediately after calving.